1985
DOI: 10.1016/s0196-0644(85)80916-1
|View full text |Cite
|
Sign up to set email alerts
|

Endotracheal versus intravenous epinephrine during electromechanical dissociation with CPR in dogs

Abstract: The dose-response curves of epinephrine given either IV or endotracheally (ET) were compared during resuscitation from electromechanical dissociation (EMD). Ten anesthetized dogs were subjected to a two-minute period of electrically induced ventricular fibrillation (VF) followed by defibrillation without CPR to produce EMD. Mechanical CPR was followed by injection of either ET or IV epinephrine. Successful response was defined as a return of pulsatile blood pressure within two minutes of drug administration. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0
1

Year Published

1988
1988
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(19 citation statements)
references
References 20 publications
0
18
0
1
Order By: Relevance
“…3 Endotracheal tube administration often requires the use of higher drug doses (compared with IV), 8 which can create airway irritation and interfere with gas exchange.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Endotracheal tube administration often requires the use of higher drug doses (compared with IV), 8 which can create airway irritation and interfere with gas exchange.…”
Section: Discussionmentioning
confidence: 99%
“…However, the need for higher drug doses, problems related to particle size, and distribution of drug to the lung periphery can hinder the effectiveness and/or usefulness of this type of drug delivery. [7][8][9][10] Liquid ventilation (LV), while providing a revolutionary mode for respiratory support, has also been shown experimentally to be an effective alternative means for drug administration. [11][12][13] For example, priscoline and gentamicin have been delivered to the uninjured lung of full-term animals and preterm animals with respiratory distress syndrome more effectively in this way as compared with IV administration.…”
mentioning
confidence: 99%
“…24 These studies have shown significant increases in regional myocardial blood flow, aortic diastolic pressure, cerebral blood flow, and ROSC in animals receiving 0.1 to 0.2 mg/kg as compared with those receiving 0.01 mg/kg of epinephrine. 22,[25][26][27][28][29] Furthermore, 2 series of pediatric inpatients experienced an improved rate of ROSC after receiving 0.2 mg/kg of epinephrine as the third dose during resuscitation. 4,30 However, there have been no large prospective clinical trials that established the effectiveness of HDE in cardiopulmonary arrest (CPA) of the pediatric patient.…”
mentioning
confidence: 99%
“…Other investigators have used specially designed catheters for the injections; Ralston and colleagues used a catheter with a spray nozzle to produce a fine mist of the injected solution in the distal trachea and then dispersed the mist into the lungs by two or three large volume breaths [6]. Drugs are distributed more uniformly and more deeply into the lung and are absorbed more rapidly after aerosol inhalation than after tracheal injection [9].…”
Section: Discussionmentioning
confidence: 99%